Architecture RePerformed the politics of reconstruction - Mager, Tino 19XX- (Ashgate, 2015)
First emerging at the beginning of the twentieth century, architectural reconstruction has increasingly become an instrument to visually revive a long bygone past. This book deals with the phenomenon of meticulous reconstruction in architecture. It argues that the politics of reconstruction go far beyond aesthetic considerations. Taking architecture as a major source of history and regional identity, the impact of large-scale reconstruction is deeply intertwined with political and social factors. Furthermore, memories and associations correlated with lost buildings of a bygone era are heavily influenced by their re-appearance, something which often contradicts historical events. Reconstruction has become an established way of building and dealing with the past, yet so far, there is no comprehensive scientific study on it
Literaturangaben. - Register Seite 153-155
Keywords: Geschichte; Architektur; Politik; Architecture -- Political aspects; Buildings -- Repair and reconstruction; Reproduction (Psychology); Rekonstruktion; Aufsatzsammlung